Associations of self‐efficacy, social support and coping strategies with health‐related quality of life after radical cystectomy for bladder cancer: A cross‐sectional study. (18th March 2022) - Rammant, Elke; Leung, Tung Ming; Gore, John L.; Berry, Donna; Given, Barbara; Lee, Cheryl T.; Quale, Diane; Mohamed, Nihal E.
Abstract: Objectives: Investigating associations between self‐efficacy, social support and quality of life (HRQoL) and mediating effects of coping among bladder cancer (BC) patients treated with radical cystectomy (RC). Methods: A cross‐sectional study was conducted from January 2012 to December 2014 with 99 BC patients. An online survey assessed patient characteristics, HRQoL, coping strategies, self‐efficacy and social support. A stepwise multiple linear regression model was used. Results: Self‐efficacy and social support were significantly associated with HRQoL. Complete mediation effects of adaptive/maladaptive coping strategies emerged for the associations between self‐efficacy and social support with functional well‐being (B = 0.247, 95% CI 0.119–0.374, p < 0.001; B = −0.414, 95% CI −0.526 to −0.302, p < 0.001) and total Functional Assessment of Cancer Therapy‐Bladder (FACT‐BI) (B = 0.779, 95% CI 0.351–1.207, p < 0.001; B = −1.969, 95% CI −2.344 to −1.594, p < 0.001). Maladaptive coping mediated the associations of self‐efficacy and social support with physical well‐being ( B  = −0.667, 95% CI −0.752 to −0.516, p  < 0.001) and disease‐specific symptoms ( B  = −0.413, 95% CI −0.521 to −0.304, p  < 0.001). A partial mediation effect of adaptive coping was found for the association between self‐efficacy and social well‐being ( B  = 0.145, 95% CI 0.016–0.273, p  < 0.05). Social support was significantly associated with emotional ( B  = 0.067, 95% CI 0.027–0.108, p  < 0.001) and social well‐being ( B  = 0.200, 95% CI 0.146–0.255, p  < 0.001). Conclusion: Interventions should tackle self‐efficacy, social support and coping strategies to improve BC patients' HRQoL.